Fashion Valet / Muhammad Bashri Bukhari - Bukhari, Muhammad Bashri (2020)
This case study is about FashionValet. The founder of this company is a pair of spouse who are Datin Vivy Yusof with her husband, Dato Fadzarudin Anuar. The purpose of this case study is to learn and gain more about entrepreneurship. The case study was conducted by Muhammad Bashri Bin Bukhari. One of the components in the report is business description. In business description, the reasearcher include the business background, business milestone and also personal biodata of the choosen entreprenuer. The other component is entrepreneurial characteristics that the reseacher need to identify from entreprenuer’s characteristics through Personal Entrepreneurship Competencies (PECs). PECs need to be highlighted because PECs are in the syllabus of Fundamental of Entreprenuer (ENT300). Last but not least, the researcher attached some of the articles about the choosen entrepreneur.